Legal Politics of Party Simplification in Indonesia: A Study Based on the Political Party Regulatory Model - Hidjaz, Muhammad Kamal; W.W. Mamonto, Moch Andry; Buana, Andika Prawira (International Journal of Criminology and Sociology, 2022)
Although the idea of simplifying the party system is a noble endeavour, the choice of legal politics for simplifying political parties must be democratic and adhere to the model of structuring political parties with the right regulatory model. Therefore, this paper aims to identify the nature of political law and regulatory models for the simplification of the party system applied in Indonesia. This research is normative legal research which focuses on the study of statutory regulations and doctrines, while the research is descriptive-exploratory with statutory and conceptual approaches. The data used are secondary data consisting of primary and secondary legal materials. The data obtained were processed and analyzed qualitatively, comprehensively, and completely. Based on the identification results, the idea of a political direction for simplifying the party system in Indonesia began in the general election period of 2004, 2009, and 2014 through changes to the law on political parties and general elections. But unfortunately, the simplification of the party system and the law has not been able to be directed at a simple party system consisting of 3-5 political parties, besides that the simplification of the party system has also not been focused on simplifying the party system participating in the General election. Every shift in legal politics from the simplification of the party system during the general election shows the democratic nature of legal politics and adopts a simplified legal model from the party system prescription model, the licensing model, the promotion model, and the protection model.